Dynamically Tuneable Reflective Structural Coloration with Electroactive Conducting Polymer Nanocavities. Issue 49 (8th October 2021) - Rossi, Stefano; Olsson, Oliver; Chen, Shangzhi; Shanker, Ravi; Banerjee, Debashree; Dahlin, Andreas; Jonsson, Magnus P.
Abstract: Dynamic control of structural colors across the visible spectrum with high brightness has proven to be a difficult challenge. Here, this is addressed with a tuneable reflective nano‐optical cavity that uses an electroactive conducting polymer (poly(thieno[3, 4‐b]thiophene)) as spacer layer. Electrochemical doping and dedoping of the polymer spacer layer provides reversible tuning of the cavity's structural color throughout the entire visible range and beyond. Furthermore, the cavity provides high peak reflectance that varies only slightly between the reduced and oxidized states of the polymer. The results indicate that the polymer undergoes large reversible thickness changes upon redox tuning, aided by changes in optical properties and low visible absorption. The electroactive cavity concept may find particular use in reflective displays, by opening for tuneable monopixels that eliminate limitations in brightness of traditional subpixel‐based systems. Abstract : Electrochemically tuneable structural coloration is demonstrated based on an optical cavity with a conducting polymer based on thienothiophene as an electroactive spacer layer. Synergistic effects of optical properties and thickness changes enable low‐voltage tuning of the structural color across the whole visible range with high and similar reflectance for all the redox states.